DEVELOPMENT OF GUIDANCE ACCORDING TO BUDDHIST EDUCATIONAL ADMINISTRATION IN SECONDARY EDUCATION - ประชากุล กฤษณา; ศิริวรรณ อินถา; บัวศิริ อำนาจ (Journal of MCU Nakhondhat, 2019)
This research aims; 1) to study principles, concepts and theories of guidance in secondary education, 2) to study Buddhist principles supporting the guidance, and 3) to develop the guidance according to principles of Buddhist educational administration in secondary education. The data of this qualitative research were collected from documents, in-depth interviews with 10 guidance teachers, 12 model teachers and experts, and focus group discussions with 9 key-informants, and then analyzed by content analysis. The results of the study found that: They can access importand and necessary information for making their decision to do what is suitable to them. The scope of guidance has 3 aspects; 1) In education; to develop students in education in their capability, 2) In career, students learn and understand the world of diverse careers and have a positive attitude to the right career, and 3) In life and society, to develop student in emotional maturity, positive attitude to life and skills, and to live a life in society peacefully and happily. The Buddhist 3 principles: 1) The Four Paths of Accomplishment consisting of aspiration, effort, dedication, and investigation, that could lead to the success, 2) 3 essential doctrines consisting of studying the texts and scriptures, practical aspect of the true doctrine, and realizable aspect of the true doctrine, that could help in career, and 3) 4 virtues for a good household life to support the guidance of life and society consisting of truth and honesty, taming and training oneself, tolerance, and generosity. The essence consisted of 6 main contents; 1) Vision, Core Curriculum of Basic Education 2008, 2) Guidance Activities, Core Curriculum of Basic Education 2008, 3) Measurement and evaluation of guidance activities, 4) Program of guidance for learner development, 5) Handbook of guidance activity plan for development of the second year students in junior secondary school, and 6) 3 units of guidance activity plan structure: Unit 1; Education integrated with The Four Paths of Accomplishment, Unit 2; Career integrated with the Three Essential Doctrines, and Unit 3; Life and society integrated with Four Virtues for a good household life.